PAI-1 inhibition by simvastatin as a positive adjuvant in cell therapy - de Faria, Carolina Arruda; Zanette, Dalila Lucíola; Silva, Wilson Araújo; Ribeiro-Paes, João Tadeu [UNESP] (Springer Nature, 2019)
Cell therapy (CT) can be briefly described as the use of cells or cell components in the treatment of diseases. One of the main challenges in establishing new cell types for therapy is the low survival rates of homing cells. Glycoprotein plasminogen activator inhibitor 1 (PAI-1) is a key regulator of the plasminogen activation system, and also an essential mediator of mesenchymal stem cell (MSC) post-transplant survival rate in the target tissue. It was previously observed that the survival of cells infused into the transplanted tissue increase in the presence of PAI-1 neutralizing antibodies. Simvastatin acts at several levels in the protein cascade regulating PAI-1 levels. Thus, simvastatin-induced reduction of PAI-1 levels has a therapeutic potential by modulating the main processes involved in the creation of an inhospitable environment during the process of injury (fibrosis and cell migration). In this way, simvastatin modulates process such as migration, that plays a key role in homing and engraftment of cells after cell therapy. Due to this modulatory effect, research groups proposed the use of simvastatin as an adjuvant in different cell therapy approaches. These observations allow the proposition of the potential use of simvastatin, and possibly other statins, as an adjuvant in cell therapy, due to a mechanism of action that acts in the tissue microenvironment, promoting a better efficiency of the homing and, as a consequence, an enhancement of the paracrine effects of the stem cells in the process of tissue regeneration.
Keywords: Cell migration; Cell therapy; Engraftment; Homing; Plasminogen activator inhibitor 1; Simvastatin